(untitled) (Web of Teachers: Inderscience Research, 2024)
This article provides the basics of creating and using an interactive electronic training course based on multimedia technologies. The article emphasizes the need to use interactive e-learning courses, how to create interactive e-learning courses and procedures in the learning process, and lecture sessions.